Estudo clínico comparativo entre a esofagocardiomiotomia de Heller convencional associada a cardiopexia de Hill e fundoplicatura anterior de dor com a esofagocardiomiotomia de heller isolada realizada por vídeo-laparoscopia no tratamento crúrgico do megaesôfago - Pinheiro, Fernando Antonio Siqueira (1998)
The aim of this study is to evaluate the use of the Heller esophagocardiomyotomy (HECM) in the megaesophagus surgical treatment comparing the HECM associated with the Hill cardiopexy (HCP) and the Dor anterior fundoplication (DAFP). with the isolated HECM performed through videolaparoscopy (VL). Ninety patients with achalasic or chagasic megaesophagus, 1, II or III degrees, were analysed and operated in the Digestive Surgery Serviee at the Édouard Herriot hospital of the Claude Bernard University, Lyon-France, in the Walter Cantídeo University Hospital at the Medicine School of the Federal University of Ceará and in the General Surgery Service of the Dr. José Frota Institute Hospital, Fortaleza-Ceará, from january, 1981, to november, 1996. Fifty-nine patients (Group 1) submitted to lhe HECM associated to the HCP and the DAFP were analysed in a retrospective study. From those, 45.76% were men, 54.24% were women, and the average age was 44.86 +/- 1.91 years. Thirty-one patients (Group 2) submitted to the isolated HECM carried out through VL were studied prospectively. 41.94% of the patients were men and 58.06% were women, with the average age of 46.6l +/- 3.09 years. Both groups were analysed by evaluating the thecnical and tactical aspects of the operations, as well as, the clinical and functional results ( radiologic study of the esophagus, manometry and esophageal pHimetry ). The operation was technically feasible in all the patients of Group 1 and in 30 patients of Group 2, occuring, in this group, the only conversion case into laparotomy due lo an esophagic mucosa perforation. There were 10.16% of complications in Group 1 (3 mucosa perfurations, 1 left subfrenic abscess, 1 right frenic nerve paralysis. 1 abdominal wall infection and 6.4% in Group 2 (2 mucosa perforations). The mortality was none in both groups. The patients submitted to the isolated HECM performed through VL showed signifícantly more satisfactory results as the regards the surgical time analyses, the oral diet start and the hospital stay. The radiologic study presented a light decrease of the esophagic caliber in 59.3% of the Group 1 patients and 54.8% of the Group 2 patients. At the esophageal manometry, the HECM ( isolated or associated with HCP and the DAFP ) produces a significative decrease of the lower esophageal sphincter pressure (LESP), dropping from 6.48 kPa to 1.61 kPa in Group 1 (p<0.01) and from 5.57 kPa to 1.23 kPa in Group 2 (p<0.01). The postoperative LESP showed to be significantly higher in the patients submitted to the HECM associated with the HCP and the DAFP than in those submitted to the isolated HECM, 1,61 kpa 1,23 kPa respectively (p<0.05). The esophageal pHmetry presented low reflux rates in both groups 12.35% in Group 1 and 11.54% in Group 2). The clinical evaluation detected good results in 86.20%, of the Group 1 patients and in 89.65% of the Group 2 patients. In Group 1, 10.34% showed a regular result (4 with minor esophagitis and 2 with occasional dysphagia) and 3.45% showed a relapsing result. In Group 2, 10.35% presented a regular result (1 with minor esophagitis and 2 with occasional dysphagia). The average follow-up of these patients was 41.68 months in Group 1 and 20.24 months in Group 2.